Counterfactual analysis of extreme events in urban flooding scenarios - Xiaolan Chen; Hongtao Li; Haijun Yu; Enguang Hou; Sulin Song; Hongjian Shi; Yikai Chai (Journal of Hydrology: Regional Studies)
Study region: Jinan City, Shandong Province, China. Study focus: Applied the counterfactual method, using three extreme rainfall events, to simulate the flood risk. Scenario 1 and Scenario 2 were based on actual events that occurred in Zhengzhou City, and Scenario 3 was constructed using design patterns with return periods of 100-year, 200-year and 500-year. Utilizing a 1D-2D coupled hydrodynamic numerical model to simulate the flood inundation under these scenarios. New hydrological insights for the region: The inundation area in Jinan under Scenario 1 was reduced compared to the actual in Zhengzhou, but the average flood depth was higher. Furthermore, the distribution pattern of flood depth remained consistent across all three scenarios. Notably, in Scenario 1, the flood depths exceed a 500-year event, while the area of inundation is less than a 100-year event. However, in Scenario 2, the flood depths and area of inundation both exceeded a 500-year event. The outcomes highlight that the differing spatial distributions of terrains among different cities, even under the same rainfall scenario, elicit varying hydrological responses, which significantly affect the distribution of flood hazards. The intensity of rainfall and its spatiotemporal distribution patterns profoundly influence the extent of the inundated areas and depths. This study provides valuable insights for urban hydrology and flood risk management, helping to enhance the resilience of urban areas in responding to extreme weather events.